2011
DOI: 10.5296/ajfa.v3i1.633
|View full text |Cite
|
Sign up to set email alerts
|

Causal Relationship between Macro-Economic Indicators and Stock Market in India

Abstract: This paper investigated the market efficiency and causal relationship between selected Macroeconomic variables and the Indian stock market during the period January 2005 to February 2011 by using Ljung-Box Q test, Breusch-Godfrey LM test, Unit Root test, Granger Causality test.The study confirms the presence of autocorrelation in the Indian stock market and macro economic variables which implies that the market fell into form of Efficient Market Hypothesis. Further the Granger-causality test shows evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…If a firm is dealing in export, than exchange rate variability can have a bearing on the cash flows. Tripathy (2011) found that the variability of the exchange rate affects the trading volume. Index of industrial production (IIP) is another important indicator chosen for the study, which reflects the performance of the industrial sector.…”
Section: Introductionmentioning
confidence: 99%
“…If a firm is dealing in export, than exchange rate variability can have a bearing on the cash flows. Tripathy (2011) found that the variability of the exchange rate affects the trading volume. Index of industrial production (IIP) is another important indicator chosen for the study, which reflects the performance of the industrial sector.…”
Section: Introductionmentioning
confidence: 99%
“…The different conclusions have been provided by the various conducted studies according to the selection of variables, methodologies, techniques and tests used. Here, we discussed some previous research works and their conclusions that are related to our research work [13][14][15][16][17][18][19][20][21].…”
Section: Relationship Between Macroeconomic Variables and Stock Markementioning
confidence: 99%
“…Figure 1 shows the movement of the share price of seven palm oil issuers in Indonesia from 2010 to 2016. Tripathy (2011) conducted a study that showed that there was a correlation between the Indian capital market and macroeconomic variables. Adebiyi et al (2009) in his research for a case study in Nigeria showed that oil prices negatively affected stock returns, which means that rising oil prices will reduce stock returns in Nigeria.…”
Section: Introductionmentioning
confidence: 99%